THE EVOLUTION OF ASTHETIC VIEWS IN EARLY CHRISTIANISM - Gulnora Khudayberganova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
as a spiritual practice, asceticism, despite the fact that it exists in almost all religions in its own way, each of them gives its own meaning and significance to this state (phenomenon). At the same time, there are general aspects of the ascetic state. This article analyzes the evolution of the phenomenon of asceticism in Christianity. The essence of asceticism in Christianity, as well as the mutual and different aspects of its directions, were revealed on the basis of research conducted in this area by Eastern and Western scientists